2008
DOI: 10.1021/jp800165q
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of Conformational Isomerization Energy Thresholds in Serotonin

Abstract: Stimulated emission pumping-population transfer (SEP-PT) and hole-filling (SEP-HF) spectroscopies were used to determine the energy thresholds to isomerization between thirteen reactant-product conformer pairs in the biomolecule serotonin (SERO). Serotonin is a close structural analog of tryptamine (TRA), differing in having a hydroxyl group in the 5 position of the indole ring. A previous spectroscopic study (LeGreve; et al. J. Am. Chem. Soc. 2007, 129 (13), 4028) identified eight conformational isomers of SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 22 publications
(53 reference statements)
1
35
1
Order By: Relevance
“…LeGreve et al [26] have proposed eight conformational isomers of serotonin while the same authors [34] have suggested that serotonin exist in 13 conformations. Cabezas et al [35] have found only three conformers from microwave spectroscopy.…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
“…LeGreve et al [26] have proposed eight conformational isomers of serotonin while the same authors [34] have suggested that serotonin exist in 13 conformations. Cabezas et al [35] have found only three conformers from microwave spectroscopy.…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
“…Yet, experimental techniques exist to measure conformational distribution [47], and even conformational energetics [149]. Even though conformational distributions have indeed been measured for a few peptides [47,71,72,125,126], conformational energetics have been measured only for slightly simpler systems [149,180,181]. Conclusions about conformational energetics from the majority of experiments have thus been limited so far to identifying major and minor conformations of the distribution.…”
Section: Lessons From the Confrontation mentioning
confidence: 99%
“…The control of the excess energy deposited in the system, especially in UV/UV pump-dump experiments, together with the detection of the isomerisation (or population transfer) threshold, ultimately led to a convincing measurement of the relative energies of the conformers observed, together with the height of the barriers between them. This has been carried out for small biomolecules [149,181], but not yet for molecules of the size of a peptide.…”
Section: Probing the Flexibilitymentioning
confidence: 99%
“…There have been a lot of experimental and theoretical studies on multiconformer biomolecular systems in gas phase [1][2][3][4][5]. Among all the neurotransmitters serotonin has been studied extensively whose flexible ethylamine chain has attracted the most for the quantum chemical investigations.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of current study is to explore the effect of pyridyl nitrogen in the ring on the conformational landscape of 7-azaserotonin. Moreover, three recent reports, one on the synthesis and photophysical study of 7-azaserotonin in condensed phase [18] and the other two on the conformational study of jet-cooled serotonin [3,5] encouraged us to investigate this molecule in gas phase by quantum chemical methods. We hope this study will compliment theoreticians to design appropriate force field method for 7-azaserotonin-receptor interaction and spectroscopists to assign the experimental spectra.…”
Section: Introductionmentioning
confidence: 99%